Iqra’ fun learning: a gamification edu apps / Idayu Nazri - Nazri, Idayu (2022)
Covid-19 has had such a big influence on everyone since it struck all around the world, including Malaysia. Malaysia therefore began to embrace a new norm, requiring the wearing of face masks when outside, as well as online learning, practicing social distancing, and other measures. These days, mobile learning is being used as a technique of education. Furthermore, as technology advances, everyone, including youngsters, is increasingly reliant on mobile devices. On the other hand, although Iqra learning is a need for all Muslims since it is a fundamental skill in recognizing hijaiyah letters, certain teaching methods nowadays may not pique children's interest in studying it. Iqra Fun Learning is a gamification-enhanced learning and play experience for children. Gamification elements are aspects that can draw children's attention to learn while keeping them from becoming bored throughout the process. Gaining badges after completing each assignment from the learning and play phases is one of the gamification components that has been put into the application. The RAD technique was used to create this application since it is the best procedure for designing mobile applications. In terms of learning material, an interview with five children's guardians is being conducted to determine what sort of learning content is appropriate for their children, as well as what interests them the most. Unity Software is used to create the application, which is a real-time development platform for 2D and 3D environments. Following the testing of the application with seven children and the distribution of a questionnaire to their guardians, it was discovered that 80 percent of the replies were in favour of a favourable outcome. This indicates that the application's objective has been achieved. Despite the great outcome of the application, there are still limitations that must be addressed in future development.